Application of quality tools for inventory management in a convenience store - Nunes, Rafael da Penha Tavares Gomes; Servare Junior, Marcos Wagner Jesus; Gomes, Thiara Cezana (Brazilian Journal of Production Engineering, 2022)
Properly controlling inventory is one of the ways to be successful in any field of activity, however, it is possible to see that many companies are still insufficient in this area, bringing a negative impact on their cash flow and materials, generating non-specific waste. It is known that the micro and small business market is responsible for moving a large part of the country’s economy, and for this reason, the study is justified by the need to emphasize processes that often seem to be irrelevant in this market, such as control of the logistical flow in a convenience store. The chosen company is a company in the retail merchandise trade sector located in the state of Espírito Santo, in the municipality of Vila Velha. With approximately 2 years in the market, the convenience store sells snacks, beverages, cigarettes and other products. In this sense, using control and management tools, it is possible to improve the process of entry and exit of goods at the convenience store portrayed, as well as the financial flow and demand forecast. To achieve the objective of this work, it is necessary to use tools ABC curve, Ishikawa diagram, 5S and 5W2H.